Dust control in livestock buildings with electrostatically-charged water spray - Almuhanna, Emad Ali (Kansas State University, 2007)
This research was conducted to investigate the potential of charged-water spray in controlling dust in livestock buildings. Specific objectives were to: (1) develop a method to measure the electrostatic charge of airborne particles; (2) characterize the size distribution and charge of airborne particles in a livestock building; (3) evaluate the effectiveness of charged-water spray in controlling dust concentration in enclosed spaces under laboratory conditions; (4) model the effectiveness of charged-water spray in controlling dust in an enclosed building; and (5) develop and evaluate an electrostatically-assisted particulate wet scrubber (EAPWS). A dynamic Faraday-cage sampler was developed for measuring the net charge-to-mass ratio of particles. The device involves collecting particles on a filter and measuring the charge induced. The sampler was calibrated and then used to measure the charge of dispersed particles (i.e., corn starch, NaHCO3, positively charged water spray, negatively charged water spray, and uncharged water spray). The corresponding net charge-to-mass ratios were -0.11 (SD=0.07), +0.20 (0.001), +7.24 (1.6), -6.47 (0.9), and -0.30 (0.12) mC/kg. Characterization of dust in a swine building showed mean dust concentration of 0.89 (SD=0.45) mg/m3, geometric mean diameter of particles of 9.34 μm, and geometric standard deviation of 2.11. The Faraday-cage sampler was also used in the swine building; the net charge-to-mass ratio of particles was +0.68 mC/kg (SD=0.31 mC/kg). The effectiveness of charged-water spray in reducing dust concentration was investigated in an experimental chamber. Test particles (i.e., corn starch, NaHCO3) were dispersed into the chamber and then charged water was sprayed into the chamber. The charged-water spray was significantly more effective than either the uncharged-water spray or no water spray. The removal efficiency of the charged water spray (4 min spray duration, 120 mL/min), based on mass, ranged from 88% to 92% for particles ≤ 10 µm equivalent aerodynamic diameter (EAD) and from 34% to 70% for particles ≤ 2.5 µm EAD. A model based on coagulation was used to predict the particle concentration after spraying of charged water. Predicted values of concentration and removal efficiency agreed well with measured values. A prototype EAPWS was also developed. Laboratory and field evaluations of the EAPWS indicated that it had significantly higher particle removal efficiency than either the control (i.e., no water spray) or the uncharged wet scrubber.
Keywords: Dust; Livestock; Electrostatic; Water Spray; Engineering, Agricultural (0539)